Production of amylase by rhizobia using peach palm flour as substrate - Oliveira, Arlem Nascimento de (Ciência e Tecnologia de Alimentos, 2020)
Amylases are among the most important industrial enzymes and are of great significance in present-day biotechnology. Although they can be derived from various sources, enzymes from microbial sources are generally the most required by industry. Species of the genus Bacillus are considered to be the main sources of amylases, although screening for new microbial sources is increasing all over the world. The objective of the present study was to evaluate the production of amylase by indigenous rhizobia, using peach palm flour as substrate. In this study, a completely randomized experimental design was adopted with three replicates. Pearson's correlation coefficients were calculated for medium pH, extracellular protein, cellular biomass, mean colony diameter (MCD), mean halo diameter (MHD), enzymatic index (EI) and amylolytic activity variables from the bacteria selected. Out of the 19 rhizobia strains with amylolytic activity on modified YMA, seven (36.8%) strains showed "EI" ≥ 2,1, and they were considered as good producers of amylase. The "IE" presented by bacteria INPA R-987, R-950 and R-915B were significantly lower (p < 0.01) than those shown by the INPA R-926, R-975 and R-957. The amylolytic activity varied significantly (p < 0.01) among the rhizobia strains. INPA R-975 and R-926 strains presented, respectively, the highest (1.00 U.min-1.mL-1) and the lowest (0.31 U.min-1.mL-1) activity average. In general terms, the extracellular protein was correlated positively with "EI" (r = 0.52*; p < 0.05) and "MHD" (r = 0.55*; p < 0.05). The cellular biomass showed positive correlations with amylolytic activity (r = 0.55*; p < 0.05) and "MHD" (r = 0.54*; p < 0.05), and a negative with final pH medium (r = 0.93**; p < 0.01).